Preeclampsia and placental stiffness: a systematic review of elastography as a predictive tool - I Nyoman Hariyasa Sanjaya; Wiku Andonotopo; Muhammad Adrianes Bachnas; Julian Dewantiningrum; Mochammad Besari Adi Pramono; Ryan Saktika Mulyana; Evert Solomon Pangkahila; Muhammad Ilham Aldika Akbar; Cut Meurah Yeni; Dudy Aldiansyah; Nuswil Bernolian; Anak Agung Gede Putra Wiradnyana; Sri Sulistyowati; Milan Stanojevic; Asim Kurjak (Indonesian Journal of Perinatology, 2026)
Background: Preeclampsia is a leading cause of maternal and perinatal morbidity and mortality, responsible for approximately 14% of maternal deaths worldwide. Despite extensive research, early predictive tools remain inadequate. Since the placenta plays a central role in disease pathogenesis and exhibits pathological changes before clinical onset, placental elastography—a non-invasive ultrasound technique that quantifies tissue stiffness—has emerged as a promising modality. Methods: This systematic review synthesized literature published between 2010 and 2025 on placental elastography in preeclampsia. Databases were searched in accordance with PRISMA methodology. Eligible studies using strain or shear wave elastography were analyzed, and methodological quality was assessed using the Newcastle–Ottawa Scale (NOS) for observational studies and ROBIS for the included meta-analysis. Results: Fifty-two studies were included. Across modalities, pregnancies complicated by preeclampsia consistently demonstrated increased placental stiffness compared with normotensive controls. Alterations were detectable as early as the first trimester in some cohorts, supporting the hypothesis that biomechanical placental changes precede clinical manifestations. Although techniques, timing, and stiffness metrics (e.g., Young’s modulus, strain ratio) varied, the majority reported significant associations with early- and late-onset preeclampsia. Conclusions: Placental elastography reveals quantifiable stiffness alterations that may enable earlier risk stratification for preeclampsia. However, heterogeneity in imaging protocols, modest sample sizes, and limited longitudinal validation remain challenges. Given its real-time, bedside applicability, elastography holds promise as a complementary predictive tool. Future research should prioritize multicenter prospective studies, integration with biochemical markers, and assessment of clinical outcomes to validate its role in modern obstetric care.